Workflow and Throughput of Commercial Assays to Detect Mycoplasma genitalium and Macrolide Resistance–Mediating Mutations. Issue 9 (11th September 2021) - Shah, Anika; Jang, Dan; Martin, Irene; Speicher, David J.; Lidder, Ravinder; Clavio, Avery; Ratnam, Sam; Smieja, Marek; Chernesky, Max
Abstract : Hands-on and automation times to detect Mycoplasma genitalium varied and were influenced by the numbers of specimens. One assay detected M. genitalium and macrolide resistance–mediating mutation together. Positives from the other assays required more time to perform sequencing. Abstract: Aptima Mycoplasma genitalium (MG) required the shortest and STD6 the longest time to detect MG in clinical samples. ResistancePlus MG detected MG and macrolide resistance–mediating mutations simultaneously. Times were influenced by specimen numbers. M. genitalium positives from the other 2 assays required increased time for macrolide resistance–mediating mutation sequencing.